Casting an invalid vote at the 2017 French presidential election. Issue 4 (December 2018) - Heinsohn, Till
Abstract France voted for a new president on May 7, 2017. Emmanuel Macron, the candidate for the social liberal partyEn Marche!, won in a runoff election against Marine Le Pen, the candidate for the right-wing populist and nationalist partyFront National . An enormous increase can be recorded comparing the shares of blank and spoiled ballot papers in the first round on 23 April, when no candidate won a majority, with that of the runoff election, which was held between the top two candidates less than a month later. Exceeding 11% in the 2017 runoff election all in all, invalid voting is more common than it has ever been before. In light of this, there is a strong suspicion that numerous voters—in particular those who did not vote for one of the top two candidates in the first round—decided to vote blank or spoiled their ballot paper in the second round. However, this conventional wisdom has not yet been tested empirically.